Cost analysis of post-polio certification immunization policies - Sangrujee Nalinee; Cáceres Victor M.; Cochi Stephen L. (The World Health Organization, 2004)
OBJECTIVE: An analysis was conducted to estimate the costs of different potential post-polio certification immunization policies currently under consideration, with the objective of providing this information to policy-makers. METHODS: We analysed three global policy options: continued use of oral poliovirus vaccine (OPV); OPV cessation with optional inactivated poliovirus vaccine (IPV); and OPV cessation with universal IPV. Assumptions were made on future immunization policy decisions taken by low-, middle-, and high-income countries. We estimated the financial costs of each immunization policy, the number of vaccine-associated paralytic poliomyelitis (VAPP) cases, and the global costs of maintaining an outbreak response capacity. The financial costs of each immunization policy were based on estimates of the cost of polio vaccine, its administration, and coverage projections. The costs of maintaining outbreak response capacity include those associated with developing and maintaining a vaccine stockpile in addition to laboratory and epidemiological surveillance. We used the period 2005-20 as the time frame for the analysis. FINDINGS: OPV cessation with optional IPV, at an estimated cost of US$ 20 412 million, was the least costly option. The global cost of outbreak response capacity was estimated to be US$ 1320 million during 2005-20. The policy option continued use of OPV resulted in the highest number of VAPP cases. OPV cessation with universal IPV had the highest financial costs, but it also had the least number of VAPP cases. Sensitivity analyses showed that global costs were sensitive to assumptions on the cost of the vaccine. Analysis also showed that if the price per dose of IPV was reduced to US$ 0.50 for low-income countries, the cost of OPV cessation with universal IPV would be the same as the costs of continued use of OPV. CONCLUSION: Projections on the vaccine price per dose and future coverage rates were major drivers of the global costs of post-certification polio immunization. The break-even price of switching to IPV compared with continuing with OPV immunizations is US$ 0.50 per dose of IPV. However, this does not account for the cost of vaccine-derived poliovirus cases resulting from the continued use of OPV. In addition to financial costs, risk assessments related to the re-emergence of polio will be major determinants of policy decisions.